Chilly climate perceived by female engineering undergraduates: an exploratory study using concept mapping - Kim, Tanhui; Kim, Dongil (Frontiers in Psychology, 2023)
Introduction Women still being a minority in engineering majors, they are reported to face discriminatory treatment in a collegiate environment. “Chilly climate,” referring to such a sexist environment, may have a negative impact on women’s mental health, academics, and careers. But, what exactly is it that female students in engineering perceive as chilly, and how chilly is it? This study aimed to explore the chilly campus climate perceived by female undergraduate engineering students in South Korea using the concept mapping method. Methods Semi-structured interviews were conducted with 13 participants enrolled for more than four semesters at four-year coeducational universities. After extracting 52 representative statements, the participants were asked to classify them according to content similarity and rate the influence of each statement on their perception of the chilly climate. For concept mapping analysis, multidimensional scaling analysis (ALSCAL), hierarchical cluster analysis (Ward’s method), and non-hierarchical cluster analysis (K-means method) were performed. Results Fifty-two statements were extracted under the following four clusters: (i) “Exclusion and alienation inherent in the culture (Cluster 1),” (ii) “Sexual objectification and lack of gender sensitivity (Cluster 2),” (iii) “Male-centered academic situations (Cluster 3),” and (iv) “Prejudice and generalization (Cluster 4).” A concept map was two-dimensional: an X-axis named “context dimension,” with “task: academic” and “non-task: social” at both ends, and a Y-axis named “sexism dimension”, having “explicit” and “implicit” at both ends. The order of higher scores in the influence rating is as follows: Cluster 2, Cluster 3, Cluster 1, and Cluster 4. Discussion This study is significant because it conceptualizes the subjective experience of minorities in a collegiate environment and provides influence rating results for prioritized measures. The findings will be helpful in formulating educational policies, psychological counseling, and social advocacy activities. Future research should target larger populations, and cover more diverse cultures, majors, and age groups.